Delamination identification using machine learning methods and Haar wavelets - Feklistova, Ljubov; Hein, Helle (Computer Assisted Methods in Engineering and Science, 2017)
The present paper focuses on the identification of delamination size and location in homogeneous and composite laminates. The modal analysis methods are employed to calculate the data patterns. An aggregated approach combining Haar wavelets, support vector machines (SVMs) and artificial neural networks (ANNs) is used to solve identification problems. The usability and effectiveness of the proposed technique are tested by several numerical experiments. The advantages of the proposed method lie in the ability to make fast and accurate calculations.